2013
DOI: 10.2310/jim.0b013e318292fb1e
|View full text |Cite
|
Sign up to set email alerts
|

Serum S100A12 Levels Are Correlated with the Presence and Severity of Coronary Artery Disease in Patients with Type 2 Diabetes Mellitus

Abstract: High S100A12 levels are associated with the presence and severity of CAD in patients with T2DM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 23 publications
1
20
0
Order By: Relevance
“…Accumulating evidence has disclosed high levels of several inflammatory mediators including C-reactive protein, which are present at very high levels in the peripheral blood of patients at risk of POD or POCD (Cerejeira et al, 2012;Neerland et al, 2016;Vasunilashorn et al, 2017). It is confirmed initially that human S100A12 is expressed and secreted by activated neutrophil granulocytes (Achouiti et al, 2013;Bae et al, 2014;He et al, 2015;Isoyama et al, 2015Isoyama et al, , 2016Zhao et al, 2013). In this regard, S100A12 is known to trigger a pro-inflammatory immune response by binding RAGE, thereby leading to inflammatory activation (Achouiti et al, 2013;Bae et al, 2014;He et al, 2015;Isoyama et al, 2015Isoyama et al, , 2016Zhao et al, 2013).…”
Section: Discussionmentioning
confidence: 97%
“…Accumulating evidence has disclosed high levels of several inflammatory mediators including C-reactive protein, which are present at very high levels in the peripheral blood of patients at risk of POD or POCD (Cerejeira et al, 2012;Neerland et al, 2016;Vasunilashorn et al, 2017). It is confirmed initially that human S100A12 is expressed and secreted by activated neutrophil granulocytes (Achouiti et al, 2013;Bae et al, 2014;He et al, 2015;Isoyama et al, 2015Isoyama et al, , 2016Zhao et al, 2013). In this regard, S100A12 is known to trigger a pro-inflammatory immune response by binding RAGE, thereby leading to inflammatory activation (Achouiti et al, 2013;Bae et al, 2014;He et al, 2015;Isoyama et al, 2015Isoyama et al, , 2016Zhao et al, 2013).…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies reported that LY86 was involved in obesity, inflammation, and insulin resistance [31]. S100A8 and S100A12, belonging to the calgranulin gene family, play key immune response roles in inflammatory disorders, like diabetes and cardiovascular disease [32]. In addition, S100A8 can recruit macrophages to adipose tissue during inflammation and in the setting of hyperglycemia and obesity [33, 34].…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14][15][16] The design of the mentioned studies is mainly cross-sectional and conducted in patient populations. A positive association between EN-RAGE and CHD mortality was shown in a prospective study, including patients on hemodialysis.…”
Section: Discussionmentioning
confidence: 99%